Efek pemanasan pada molases yang ditambahkan urea terhadap ketersediaan NH3, volatile fatty acid dan protein total secara in vitro - Putri Rafleliawati; Surahmanto Surahmanto; Joelal Achmadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The study aims to utilizing mollases as reducing sugar to bind ammonia from urea through maillard reaction in high temperature as a source of Non-protein nitrogen (NPN) slow release in order to improve the efficiency of NPN and of the avaibility of total protein. The study used mollases and cow rumen fluid from Ungaran slaughterhouses. The method of the study was factorial complate random design with 2x3 treatments and 3 replications. The treatments were A0B1 (mollases-urea non heated 1 hour incubation), A0B2 (mollases-urea non heated 3 hour incubation), A0B3 (mollases-urea non heated 5 hour incubation), A1B1 (mollases-urea heated 1 hour incubation), A1B2 (mollases-urea heated 3 hour incubation) and A1B3 (mollases-urea heated 5 hour incubation). The data were analyzed using analysis of variance (ANOVA). The results showed that NH3, Volatile Fatty Acids (VFA) and total protein production in different hours of incubation were significant (P<0,05), meanwhile production in mollases heat treatment and interaction between them were not significant (P>0,05). The longer the time of incubation, the lower the production. The highest NH3production was found at one hour of time of incubation. The VFA and total protein productions increased along with the increasing time of incubation with highest production was found at 5 hours of time of incubation. Keywords : Slow release, maillard reaction, NH3, VFA, protein total